Peningkatan Kemampuan Menulis Ulasan Buku Fiksi Menggunakan Model Pembelajaran Student Team Achievement Division (STAD) Peserta Didik Kelas XI MIPA 1 SMA Negeri 7 Yogyakarta - Budi Rahayu (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
This research is a Classroom Action Research (CAR) which aims to improve the writing ability of students of Class XI MIPA-1 Yogyakarta 7 Public High School in 2018/2019 through the application of the Student Team Achievement Division (STAD) learning model. This research was conducted collaboratively and participatively which was carried out in two cycles. Data collection in this study was carried out using participant observation and written tests. Based on the results of the study concluded that the application of the STAD learning model can improve motivation and writing ability. This is supported by research data that shows an increase in the percentage of completeness of the written tests conducted at the second meeting in each cycle. At the time of pre-cycle, students completeness was only 36%, after the first cycle was implemented with the STAD learning model the percentage of students' writing ability was 61% then in the cycle II action reached 91%. The application of the STAD learning model can also improve the indicators of students' ability to write grade XI MIPA-1 SMA Negeri 7 Yogyakarta in 2018/2019 Academic Year. Indicators of students' writing ability consist of cohesion, coherence and language style. In the first cycle, the students' writing ability indicator obtained a final score of 64%, meaning that the ability to write was within the sufficient criteria. In the second cycle the final score of the indicator of students' writing ability reached 90% so that it is in good criteria.